ANALYSIS OF ENGLISH LANGUAGE TEACHING TECHNIQUES FOR ENHANCING STUDENTS’LANGUAGE PROFICIENCY - Amin Irna Wati; Listyaning S; Dias Andris Susanto (Penerbit Lafadz Jaya, 2022)
The research aimed to find out (1) Teaching strategies used by teacher in improving students’ English language skills. (2) The students’perception of teaching strategy used by teacher in improving students’ English language skills. The data were conducted on August 2022 from the teacher and students of tenth grades at SMK Negeri 3 Pati. This research used descriptive qualitative method; the instruments were an observation and interview. The observation was used to observe the teacher of the tenth-grade students at SMK N 3 Pati and the interview was distributed to the students of the tenth grade. The research findings showed that the English teaching strategies used by teachers help improve students' language skills. By using Microsoft Teams, WhatsApp and several learning support media in the form of modules, teachers and students were able to find new ideas and express them every day. However, there are some students who have negative views about the teaching strategies that teachers use to improve their students' language skills. This is based on the students' disinterest and a sense of laziness and fear to learn English as a foreign language.